Engineering the spark into bacteria: Development of electroactive bacterial chassis via gene engineering and bio- hybridisation with conductive nanomaterials - Myers, Benjamin (2024)
Climate change from anthropogenic hydrocarbon fuel use is causing rapid and unprecedented changes to global environmental systems. To prevent environmental collapse, it is vital to develop technologies for producing carbon- negative energy and fuels. This is the grand scientific, industrial, and economic challenge of our time and requires novel energy production and waste valorisation strategies at all levels of society, from global- scale producers to individual households. While there is no individual solution, the unique chemical <> electricity energy conversion possibilities of Microbial Electrochemical Technologies (MET) may offer innovative routes for capturing the residual energy in waste, alongside valorising spent carbon into energy rich fuels and chemicals. However, a range of process- limiting challenges results in MET applicability mostly languishing at the laboratory scale. This thesis aims to address two of these challenges, specifically: (1) MET being bound to the intrinsic physiological properties and growth rates of native electroactive microbes, and 2) the inefficiency of biological extracellular electron transport (EET) between cells and electrodes. The work presented in this thesis employed two distinct strategies to combat these challenges. First, a gene modification strategy was used to increase the electroactive potential of the industrially relevant microorganism Cupriavidus necator. Second, a ‘biohybrid’ strategy was proposed, based on the implantation of functionalised carbon nanotubes within the outer membrane of Cupriavidus necator to augment electron exchange, in addition to the native biological electron transport mechanisms.